The Tat protein of equine infectious anemia virus is encoded by at least three types of transcripts - Noiman, Silvia; Yaniv, Abraham; Tsach, Tsvia; Miki, Toru; Tronick, Steven R.; Gazit, Arnona (Virology (New York, N.Y.), 1991)
Nucleotide sequence analysis of a cDNA library of EIAV-infected canine cells established a complex pattern of gene expression, characterized by alternatively spliced polycistronic transcripts. The EIAV tat gene product was shown to be encoded by at least three species of mRNA which differed in their ability to trans-activate the EIAV LTR upon expression in canine cells. The most active cDNA was monocistronic, consisting of three exons. The most abundant cDNA in the library contained four exons and was identical to a polycistronic transcript previously described (Noiman et al., 1990b) which contains open frames for Tat, putative Rev, and truncated transmembrane proteins. Products consistent in size with those predicted for these last two proteins could be detected in in vitro translation experiments. The third Tat message, another four-exon form, also potentially encodes an amino terminally truncated transmembrane protein. In vitro mutagenesis experiments and analysis of subgenomic and partial cDNA clones confirmed and extended previous findings that S1 sequences are essential for trans-activation and that Tat translation initiates at a non-AUG codon either in the full-length Tat message or in the genomic S1 open reading frame. The Tat protein (8 kDa) was detected in cells transfected with a Tat cDNA construct and in canine cells persistently infected with EIAV. The Tat activity of polycistronic mRNAs was lower than that of the monocistronic form, suggesting that the expression of the EIAV trans-activator may be subject to several levels of posttranscriptional control.